Correlation of Knowledge about Covid-19 Post-Immunization Adverse Events (PIAE) with Motivation To Carry Out Vaccinations - Theresia Anita Pramesti; Zainal Firdaus Wardhana (GLOBAL HEALTH SCIENCE GROUP, 2022)
The COVID-19 pandemic has lasted more than a year and is still not under control, marked by the high number of confirmed COVID-19 cases and the number of deaths. The handling of the pandemic is more focused on efforts to control transmission, one of which is by building herd immunity through the COVID-19 vaccination program. Along with the start of the vaccination program, problems arose regarding the number of hoaxes, especially regarding the Post-Immunization Adverse Events (PIAE) which raised doubts and public anxiety about being vaccinated. This study aims to determine the relationship between level of knowledge and motivation to carry out COVID-19 vaccination. This research is a descriptive correlational research with a sample of 81 people taken using purposive sampling technique. The results showed that the level of knowledge of the respondents was mostly in the adequate category, namely 43 respondents (53.1%), while the motivation of respondents in carrying out COVID-19 vaccination was mostly in the adequate category, namely 67 respondents (82.7%). Based on the results of the Spearman Rank test (α = 5%) obtained a p value of 0.001 with a correlation coefficient of 0.356, so it can be interpreted that there is a correlation between the respondent's level of knowledge about COVID-19 Post-Immunization Adverse Events (PIAE) with motivation to vaccinate against COVID-19 with a moderate correlation strength. A good level of knowledge can increase the positive and enthusiastic perception of the community so that it can also increase motivation in carrying out COVID-19 vaccinations.